Effects of Arm Swing Limitation on Knee Joint Moment during Walking —Biomechanical Analysis Using a 3D Motion Capture System - Nagasaki, Takayuki; Hori, Katsuhiro; Fukudome, Hideaki; Katoh, Hiroshi; Hamada, Terukazu; Goshima, Yokiko; Nakano, Sota; Gotoh, Kenta; Tashiro, Yuki; Noguchi, Hirotaka (Journal of Physical Therapy Science, 2012)
[Purpose] The purpose of this research was to examine the biomechanical effects of arm swing limitation on knee joint gait. [Subjects] Subjects were 10 healthy males (mean age, 22 ± 0.8 years; mean height, 173.9 ± 5.9 cm; mean weight, 67.0 ± 6.4 kg). [Methods] Knee abduction normally shows a bimodal curve. The top of the primary curve was defined as val_m1 and that of the secondary curve was defined as val_m2. Knee abduction moment, knee extension moment, GRF range, trunk rotation range, and arm swing range were then calculated at val_m1 and val_m2. Measurements were performed without arm swing limitation on a 10-m walkway (no limitation condition), and with the subjects’ arms folded in front of their chests (limitation condition). [Results] Val_m1 was 10.9 ± 2.4% of the gait cycle. Val_m1 (65.3 ± 13.1 Nm) under the limitation condition was significantly lower than that (70.0 ± 13.0 Nm) under the no limitation condition (p<0.01). In addition, the knee extension moment (71.7 ± 21.1 Nm) under the limitation condition was significantly higher than that (62.6 ± 20.4 Nm) under the no limitation condition at val_m1 (p<0.01). [Conclusion] Arm swing limitation decreases knee abduction moment, but increases knee extension moment.